Defining Heresy: the Controversy between James Foster and Henry Stebbing (1735- 1737) - Nicolas Bourgès (Revue Française de Civilisation Britannique)
From 1735 to 1737 the Baptist preacher James Foster (1697-1753) faced the orthodox Anglican Henry Stebbing ([1687]-1763) in a controversy over the definition of heresy. Their dispute reveals two distinct methods of Bible interpretation and throws light on the tensions prevailing in the eighteenth century between the established Church and Dissent, which is represented as a danger to Anglican orthodoxy by Stebbing.